ANALYSIS OF CHLOROPHYLL-A DISTRIBUTION CONCENTRATION TO DETERMINE WATER PRODUCTIVITY IN BARRANG CADDI ISLAND - Rahmat Tamrin; Hartati Tamti (LPPM Institut Teknologi dan Bisnis Maritim Balik Diwa, 2026)
This study aimed to analyze the distribution of chlorophyll-a concentration and determine the water productivity status in Barrang Caddi Island, Makassar, Indonesia. Chlorophyll-a is widely recognized as an important indicator of phytoplankton abundance and primary productivity in marine ecosystems. The study was conducted in May 2025 using two approaches, namely direct measurements through spectrophotometric analysis and remote sensing analysis based on Aqua MODIS satellite imagery processed using SeaDAS software. Water samples were collected from three sampling stations, while satellite observations were performed weekly throughout the study period. The accuracy of satellite-derived chlorophyll-a data was evaluated using the Root Mean Square Error (RMSE) method. Spectrophotometric analysis revealed that chlorophyll-a was detected only at Station 2, with a concentration of 0.068 mg m⁻³, whereas concentrations at Stations 1 and 3 were below the detection limit. In contrast, remote sensing analysis showed higher chlorophyll-a concentrations ranging from 0.740 to 1.244 mg m⁻³ during the observation period. These values indicate that the waters surrounding Barrang Caddi Island were generally characterized by moderate productivity and classified as mesotrophic. The RMSE value between laboratory measurements and satellite-derived estimates was 1.176 mg m⁻³, indicating a considerable discrepancy between the two methods. Despite this difference, remote sensing proved effective for describing the spatial and temporal distribution of chlorophyll-a over a wide area. The findings suggest that Barrang Caddi Island waters possess moderate biological productivity and have the potential to support sustainable fisheries and other marine resource management activities